Efficacy and safety of Tripterygium wilfordii hook F for chronic urticaria: a systematic review and meta-analysis - Liu Liu; Huaibo Zhao; Xiaoying Sun; Qi Zheng; Ying Luo; Yi Ru; Ying Zhang; Xi Chen; Bo Zhu; Chengqian Yin; Bin Li; Xin Li (BMC, 2018)
Abstract Background The first-line agents comprising antihistamines for chronic urticaria, are not completely satisfactory. Tripterygium wilfordii Hook F (TwHF), a Chinese herb, has been developed into several Tripterygium agents and have definite effects on autoimmune and inflammatory diseases. In chronic urticaria, however, their values of practical application remain unclear. The aim of this study was to investigate the efficacy and safety of TwHF in patients with chronic urticaria. Methods Several databases were systematically searched including PubMed, Embase, Cochrane Central Register of Controlled Trials, China Network Knowledge Infrastructure, Chinese Scientific Journals Database, Wan Fang Database, and Chinese Biomedicine. Randomized controlled trials comparing antihistamines with TwHF or Tripterygium agents in combination with antihistamines were included. Revman5.3 was utilized to calculate risk ratios (RR) with 95% confidence intervals (CI). This study was registered with PROSPERO, number CRD42018091595. Results Twenty-one trials with 2565 participants were included in this analysis. Meta-analysis showed that, when antihistamines were combined with TwHF and Tripterygium agents, the curative effect in cases of chronic urticaria was superior to that of antihistamines alone (RR: 1.40; 95% CI: 1.33-1.46). The incidence rates of gastrointestinal disorder (RR: 2.91; 95% CI: 1.70-4.99) and menstrual disorder (RR: 6.00; 95% CI: 1.79-20.13) in drug combination groups were higher than those in controls, while other adverse events were similar between the two groups. After treatment, Dermatology Life Quality Index (RR: 1.23; 95% CI: 1.09-1.40), quality of sleep (RR: 1.50; 95% CI: 1.07-2.12), and daily activity (RR: 1.49; 95% CI: 1.25-1.78) were all improved. Furthermore, drug combination groups demonstrated less relapse (RR: 0.34; 95% CI: 0.25-0.45). Conclusions TwHF and Tripterygium agents, in combination with antihistamines, appear to be more effective than antihistamines alone. Nevertheless, adverse events cannot be ignored. Large sample, multi-center, high-quality clinical studies are needed to verify the exact effects and safety of TwHF and Tripterygium agents in treatment of chronic urticaria.